Proposal for a tailored stratification at baseline and monitoring of cardiovascular effects during follow-up in chronic phase chronic myeloid leukemia patients treated with nilotinib frontline. (November 2016) - Breccia, Massimo; Arboscello, Eleonora; Bellodi, Andrea; Colafigli, Gioia; Molica, Matteo; Bergamaschi, Micaela; Massaro, Fulvio; Quattrocchi, Luisa; Sarocchi, Matteo; Spallarossa, Paolo; Alimena, Giuliana
Abstract: Nilotinib was approved for chronic myeloid leukemia patients in chronic phase or accelerated phase after resistance to imatinib or as frontline treatment. The drug, as other tyrosine kinase inhibitor has a specific safety profile with possible occurring metabolic side effects, such as increased glycaemia and cholesterol level, that may result, in predisposed patients, in an increased rate of cardiac and vascular disorders. The objectives of this paper were to focus on the optimal procedures to perform at diagnosis in order to identify patients at risk of possible events and the correct monitoring procedures in order to prevent and manage metabolic and cardiovascular adverse events. Several national haematologist and cardiologist reviewed the literature, analysed levels of evidence for each topic and, after extensive discussions presented their proposals based on current international guidelines.